Management of recalcitrant oral pemphigus vulgaris with CO 2 laser - Report of two cases - Bhardwaj Ashu; Joshi Monika; Sharma Deepak (Wolters Kluwer Medknow Publications, 2010)
Laser has been used efficiently for treatment of oral lichen planus, leukoplakia, aphthous ulcers and oral manifestations of HIV. Two cases of recalcitrant oral pemphigus vulgaris that were successfully treated with CO 2 laser are described. The patients had been treated by a dermatologist with pulse therapy of methyl prednisolone and cyclophosphamide over a period of 6 to 8 months, but the clinical course was characterized by episodes of painful flare-ups and nonresponsiveness. The patients were extremely uncomfortable with recurrent oral lesions. CO 2 laser at low power was used to irradiate the lesions. It was shown to be effective in relieving pain and healing of lesions, with nonrecurrence. To the best of our knowledge, this is the first case report of such a treatment of oral pemphigus vulgaris. Further clinical studies are warranted to confirm efficacy and to optimize the treatment protocol.